Endoscopic negative pressure therapy as a salvage treatment for management of post-surgical anastomotic leaks without ostomy after colorectal resection - Kantowski, Marcus; Perez, Daniel; Bellon, Eugen; Rösch, Thomas; Ramouz, Ali; Tachezy, Michael; Scognamiglio, Pasquale (Scientific reports, 2025)
Anastomotic leakage (AL) after lower gastrointestinal surgery remains a serious complication with an incidence of 3-30%. Influencing factors include perfusion deficits, tension, inflammation, malnutrition, medications, and previous therapies. Surgical technique and type of anastomosis are also crucial. While various strategies for early detection and management exist, endoscopic negative pressure therapy (ENPT) has shown promising therapeutic benefits. This study evaluates the technique and outcomes of ENPT for treating AL. In this retrospective analysis, 59 patients with grade B AL following rectal resection between June 2016 and February 2022 were included. Patients had endoscopically or radiologically confirmed AL with pelvic abscess and were treated with ENPT. Exclusion criteria included relaparotomy, CT-guided drainage, sealant use, and irrigation without ENPT. Outcomes included leakage closure, abscess recurrence, sepsis, ostomy closure rate, and complications. Of the 59 patients, 16 received ENPT without an ostomy; 10 of these achieved complete healing. Median ENPT duration was 4 weeks. Higher anastomosis levels correlated with better healing. Factors such as leak type, abscess size, and chronicity influenced outcomes. Reported complications included rectovaginal fistula and anastomotic stenosis. ENPT is a safe and effective approach for AL, often avoiding permanent ostomies. A structured, endoscopy-led treatment strategy is essential.
Online veröffentlicht: 31. Oktober 2025
Gesehen am 09.02.2026